BEBERAPA FAKTOR YANG MEMPENGARUHI KEJADIAN KANKER SERVIK DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Aulia, Nurwathon; Nurlaela, Sri; Basuki, Dyah Retnani (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2009)
Cerviks cancer is a cancer that attack cerviks of the uterus, an area in woman reproduction organ that is an entrance through the uterus, place between uterus and vagina. Data from RSUD Prof. Dr.Margono Soekarjo, Purwokerto showed that there was an increasing number in cerviks cancer case. The purpose of this research was to know the risk factors that influence cerviks cancer case in RSUD Prof. Dr. Margono Soekarjo, Purwokerto. This research used of observational with case control study approach. Case group was all patients diagnosed cerviks cancer from June until November 2008 in RSUD Prof, Dr. Margono Soekarjo, Purwokerto and the control group was the patient who did pap smear check up from June until November 2008 in RSUD Prof. Dr. Margono Soekarjo, Purwokerto but the result wasn?t cerviks cancer. The number of populations were 64 people with 32 cases and 32 control. Variable researched consisted of education, marriage age, parity and oral contraception. Data analysis used was univarial, bivariat with chi square and multivariat with double logistic regression. The result of this research showed factors related with cerviks cancer case were education (p=0,00; OR=7,89; CI 95%=2,40-25,85), marriage age (p=0,00; OR=6,33; CI 95%=2,03-19,68) and parity (p=0,00; OR=11,66; CI 95%=2,37-57,36). The most influence factor in cerviks cancer case was parity. According to that result, it is suggested to the people to control the number of kids (less than 4 children) by using family planning programme that?s proper to each individual and delay the marriage age.